The Interplay Between International Relations and Science, Technology and Innovation: An Analysis of Embraer’s International Partnerships - Maurílio Daros; Iara Costa Leite; Vitelio Marcos Brustolin (Estudos Internacionais, 2023)
International partnerships have been fundamental to Embraer’s technological advancement. The very creation of the company was only possible due to prior support received from specialized institutions in countries such as the United States, with governmental support. Even so, academic works on Embraer focus very little on its international agreements. This article maps and systematizes literature on international partnerships involving Embraer retrieved by Scopus, Scielo and the CAPES Thesis and Dissertation Catalog. In addition to presenting quantitative data that corroborates the finding on low participation of specific literature on international partnerships involving Embraer, this article demonstrates that almost none of the articles retrieved by the search are from the field of International Relations. In general, concepts and theories on which the mapped literature relies assume a purely transnational component in the partnerships without taking into account, for instance, the role of states in supervising international knowledge flows. Contributions made by the literature, while relevant to understanding business partnerships involving knowledge flows, do not necessarily consider the uniqueness of such flows when they cross national borders. Furthermore, it is demonstrated that the mapped literature does not take the partnership axis (North-South or South-South) as a relevant variable for effectiveness.